¿Usted está borracho o temulento?: Ebriedad, civilité y cultura letrada en Argentina - Sergio Carlos Pastormerlo (Orbis Tertius, 2008)
In 1887 an unexpected and unwelcome poem, El borracho, was published in Buenos Aires. At that time, its author, Joaquín Castellanos, left poetry for politics. During the three following decades, the poem spread successfully in the new circuit of popular criollista literature. In 1923 Castellanos returned surprisingly to literature -to a very different literature from that of his youth - with a strange new edition of El borracho. Full of explanatory notes, the new edition replaced the original title with a euphemism which certainly demanded explanations as well: El temulento. Taking the singular anachronisms in Castellanos' poem as a starting point and following Norbert Elias' thesis on the "civilizing process", this article analyzes the relationships between drunkenness and barbarism established by the lettered culture in the Río de la Plata before its democratization -symbolically legitimized in the cult of Parisian bohemia- dissolved them in the last years of the nineteenth century